2018
DOI: 10.4103/jcrt.jcrt_1349_16
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the dose perturbation effect for therapeutic beams with the presence of a 1.5 T transverse magnetic field in magnetic resonance imaging-guided radiotherapy

Abstract: In MRI-guided cancer radiotherapy, the dose perturbation effects for therapeutic beams are relatively obvious, and the beam energies of therapeutic beams have large impacts on the magnetic-induced dose perturbations with the presence of a 1.5 T transverse magnetic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Apoint of contention is the proven dose perturbation effects of an MF on carbon ion and proton beams. Dosimetric studies have shown that there is dose distribution disruption at the air-tissue interface when an MF of 1.5 T is applied in photon beams, although its significance in carbon ion and proton beams is yet to be shown 8. On the contrary, another dosimetric study observed minimal changes in photon energy deposition even for an extremely strong MF of up to 70 T 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoint of contention is the proven dose perturbation effects of an MF on carbon ion and proton beams. Dosimetric studies have shown that there is dose distribution disruption at the air-tissue interface when an MF of 1.5 T is applied in photon beams, although its significance in carbon ion and proton beams is yet to be shown 8. On the contrary, another dosimetric study observed minimal changes in photon energy deposition even for an extremely strong MF of up to 70 T 16.…”
Section: Discussionmentioning
confidence: 99%
“…Inaniwa et al reported significantly reduced cell survival upon adding a longitudinal MF but interestingly not within a perpendicular MF 6,7. Furthermore, two other reports have shown a Bragg peak shift and dose perturbation upon employing an MF in proton beam radiotherapy;8,9 yet the biological effects of an MF have not been thoroughly evaluated and further research on possible interactions is warranted.…”
Section: Introductionmentioning
confidence: 99%
“… 35 Another similar prospective follow-up study found that long-term smoking more than 8 years was associated with increased risk of cervical intraepithelial neoplasia grade 3 or more. 36 …”
Section: Discussionmentioning
confidence: 99%
“…The link between smoking and cervical cancer has been well elucidated, with smoking influencing the incidence of CIN 3 and invasive cervical cancer [ 6 , 54 , 61 ]. This positive correlation is due to the direct mutagenic effect of nicotine (decomposed product of cigarettes) on the DNA in squamous cells.…”
Section: Epidemiology Of Cervical Cancermentioning
confidence: 99%
“…Benzo[ α ]pyrene, a constitute of tobacco, upregulates the amplification of the HPV genome, thus enhancing the integration of the viral genomes into the host’s genome [ 62 ]. The long-term effects of nicotine in vivo include the stimulation of the vascular endothelial growth factor, persistent cell proliferation, apoptosis inhibition, suppression of T lymphocyte activity and immunoglobulin levels and increased microvessel density [ 61 ].…”
Section: Epidemiology Of Cervical Cancermentioning
confidence: 99%